factorise: 27y^3 + 125z^3
Answers
Answered by
17
heya here is ur ans
we use the formula
a³+b³=(a+b)(a²-ab+b²)
![{27y}^{3} + {125z}^{3} = {(3y)}^{3} + {(5z)}^{3} \\( 3y + 5z)(9 {x}^{2} - 15yz + 25 {z}^{2} ) {27y}^{3} + {125z}^{3} = {(3y)}^{3} + {(5z)}^{3} \\( 3y + 5z)(9 {x}^{2} - 15yz + 25 {z}^{2} )](https://tex.z-dn.net/?f=+%7B27y%7D%5E%7B3%7D+%2B+%7B125z%7D%5E%7B3%7D+%3D+%7B%283y%29%7D%5E%7B3%7D+%2B+%7B%285z%29%7D%5E%7B3%7D+%5C%5C%28+3y+%2B+5z%29%289+%7Bx%7D%5E%7B2%7D+-+15yz+%2B+25+%7Bz%7D%5E%7B2%7D+%29)
{here a=3y and b=5z}
hope it helps you
we use the formula
a³+b³=(a+b)(a²-ab+b²)
{here a=3y and b=5z}
hope it helps you
Anonymous:
yo
Similar questions